2017
DOI: 10.1108/prt-02-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrochemical performances of LiFePO4-C synthesized with PEG as the grain growth inhibitor for Li-ion capacitors in LiNO3 aqueous electrolyte

Abstract: Purpose The purpose of this paper is to conduct the synthesization of LiFePO4-C (LFP-C) with fine particle size and enhanced electrochemical performance as the positive electrode material for Li-ion capacitors (LICs) with neutral aqueous electrolyte. Design/methodology/approach LFP-C was prepared by using polyethylene glycol (PEG) as a grain growth inhibitor, and the effects of the calcination temperature and PEG content on the structure and morphology of LFP-C were investigated. LICs using environment-frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has an important impact on the morphology and size of the prepared materials, which are crucial for determining electrochemical performance [34,35]. It has been reported that the grain size and morphology of the prepared samples can be well controlled by adding suitable surfactants in the solvothermal reaction process [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…It has an important impact on the morphology and size of the prepared materials, which are crucial for determining electrochemical performance [34,35]. It has been reported that the grain size and morphology of the prepared samples can be well controlled by adding suitable surfactants in the solvothermal reaction process [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%